Financial market participants expect the coronavirus pandemic to have long-lasting economic impact in Europe - Stephanie Ettmeier; Chi Hyun Kim; Alexander Kriwoluzky (DIW Weekly Report, 2020)
Market participants are generally in agreement that the coronavirus pandemic will have a severe impact on the European economy, but it is difficult to predict the length and extent of the pandemic's effects. However, using the yield curves of corporate bonds, we can reach some preliminary conclusions about the impact of the pandemic. The expectations of financial market participants are revealed in the yield curves of corporate bonds, as yields reflect risk expectations over various maturities. To analyze these expectations, we first estimated the yield curves of corporate bonds in Germany, France, Italy, and Spain and put them into context with the progression of the pandemic. This shows that the bond yields with long maturities are also increasing; therefore, financial market participants are expecting negative effects to last for at least five years. Using an event study, the effects of the European fiscal and monetary policy measures are analyzed as well. The results suggest that measures are successful when they are wide ranging and coordinated Europe-wide. Moreover, the results show that financial and monetary policies must also be coordinated to fight the economic impact of the pandemic effectively.
Keywords: E44; G12; G14; 330; COVID-19; Financial Market Expectations; Monetary and Fiscal Policy Interventions